Prevalence of Pulmonary Tuberculosis - A Baseline Survey In Central India - Rao, Vikas G. (Public Library of Science, 2012)
BACKGROUND: The present study provides an estimate of the prevalence of bacteriologially positive pulmonary tuberculosis in Jabalpur, a district in central India. METHODOLOGY/PRINCIPAL FINDINGS: A community based cross-sectional survey was undertaken in Jabalpur District of the central Indian state of Madhya Pradesh. A stratified cluster sampling design was adopted to select the sample. All eligible individuals were questioned for pulmonary symptoms suggestive of TB disease. Two sputum samples were collected from all eligible individuals and were examined by Ziehl-Neelsen smear microscopy and solid media culture methods. Of the 99,918 individuals eligible for screening, 95,071 (95.1%) individuals were screened. Of these, 7,916 (8.3%) were found to have symptoms and sputum was collected from 7,533 (95.2%) individuals. Overall prevalence of bacteriologically positive PTB was found to be 255.3 per 100,000 population (95% C.I: 195.3–315.4). Prevalence was significantly higher (p<0.001) amongst males (355.8; 95% C.I: 304.4–413.4) compared with females (109.0; 95% C.I: 81.2–143.3). Prevalence was also significantly higher in rural areas (348.9; 95% C.I: 292.6–412.8) as compared to the urban (153.9; 95% C.I: 123.2–190.1). CONCLUSIONS/SIGNIFICANCE: The TB situation in Jabalpur district, central India, is observed to be comparable to the TB situation at the national level (255.3 versus 249). There is however, a need to maintain and further strengthen TB control measures on a sustained and long term basis in the area to have a significant impact on the disease prevalence in the community.